Determining the Legal Identity of Murābaḥah: Akad Design, Documentary Sequence, and Juridical Consequences in Indonesian Islamic Banking - Alvin Yahya; Burhanudin Harahap; Solikhah Solikhah (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The accuracy of akad design is central to determining the legal identity of Sharia financing contracts in Indonesian Islamic banking, particularly in murābaḥah. While prior studies emphasize Sharia compliance, governance, and product standardization, limited attention has been given to how clause architecture and documentary sequence affect whether murābaḥah remains legally identifiable as a sale-based contract. This article examines three issues: the role of akad design in clarifying legal relations between banks and customers; the juridical consequences of inaccurate design, including nullity and wanprestasi; and the use of Religious Court decisions as empirical references for harmonizing civil law, Sharia principles, and regulatory frameworks. Using a normative-doctrinal approach, the study analyzes the Indonesian Civil Code, Law No. 21 of 2008, Law No. 4 of 2023, POJK provisions, KHES, DSN-MUI fatwas, OJK standards, and two Pekanbaru Religious Court decisions. The findings show that murābaḥah’s legal identity depends on coherence between subject matter, price, margin, procurement sequence, ownership or control, wakālah authority, and handover documentation. Inaccurate design leads to different consequences across validity and performance tracks. The study identifies recurring documentary failures and argues for a shift from macro-level compliance toward micro-level contractual architecture, emphasizing stronger pre-akad disclosure, coherent documentary chains, and clearer separation between validity and performance in dispute resolution.